Presencia del mito clásico en la poesía de Jorge Luis Borges - Alvear Castillo, Britney Carolina (2025)
This research characterizes the presence of classical myth in the poetry of Jorge Luis Borges. His work has drawn enormous critical attention for its spiritual, metaphysical, intellectual, philosophical, cabalistic, and above all, mythical representations. The proposed methodology used a qualitative approach, adopting a bibliographic design at the basic and descriptive research level. The selected corpus consisted of Borges's complete poetic works. To analyze and interpret texts associated with classic myth, the study used hermeneutic methods and content analysis. The research found frequent, both direct and indirect, references to Greco-Latin myths in Borges's poetry. These appear primarily through intertextual techniques. The study identified recurring mythical symbols such as characters, places, and spaces, reflecting Borges's ongoing fascination with these elements. Borges persistently explores the concepts of time, identity, and destiny through this mythic lens. Using Gérard Genette's theoretical framework, the research shows that Borges's poetry engages in transtextuality. This process generates new symbolic meanings and resemanticizations of classical myth as a postmodern linguistic strategy.